Ensino médio no estado de São Paulo: desafios na escolarização de alunos com deficiência - Cruz, Rosangela Aparecida Silva da (Universidade Federal de São Carlos, 2011)
The objectives of this study were writing and reflecting about: a) the treatment given to students with deficiencies by school in secondary education; b) the school census statistic data regarding early enrollments for secondary and special education nationwide and in the State of São Paulo. We followed a qualitative approach, analyzing official documents of the scholar census of different established governments, and using the group focus technique we interviewed three special education teachers and six regular education teachers. We also performed four individual interviews with high school students with deficiencies two of them also attended the resources classrooms. The analyzed data showed the increasing number of enrollments in high school and special education showed the evolution of enrollments in high school and special education (by age), and the advances and ruptures of enrollments in high school (by grade). We reviewed teachers and students' testimonials in four thematic axes: a) the inclusive classroom context; b) the resources classroom context; c) teachers' work conditions; d) permanency conditions in public school. The results we found reveal that challenges of SEE-SP are related to the expansion of resources classroom attendance to places near students' houses as it is related to the structure of school transport. This study can contribute to discussions about limits and challenges of education in the State of São Paulo. The inclusive classroom and the resources classroom could become a reality that relies on more than guaranteed school access, because offering students conditions to stay in school is utterly necessary, as well as providing better conditions for the teachers' work.
Keywords: Educação especial; Direito à educação; Sala de Recursos; Condições de trabalho docente; Right to education; High school; Special education; Resources classroom; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL